Pengembangan Bahan Farmasi: Pengaruh Variasi Suhu Pengeringan Terhadap Sifat Fisik Serbuk Kering Labu Siam - Husni, Patihul; Tryani Sutisna Putri, Sussy; Erika Herawati, Irma; Christiningtyas Eryani, Mikhania (JURNAL FARMASI GALENIKA, 2024)
Chayote (Sechium edule (Jacq). Swartz) is potential to be a pharmaceutical material.  Therefore, this study aimed to determine the effect of drying temperature variations on the physical properties of dry chayote powder. The temperatures used in the drying process are 100 ºC, 80 ºC, and 60 ºC. Evaluation of dry chayote powder includes organoleptic test, water content, flow time, angle of repose, compressibility index, and particle size distribution. The results showed brown powder in color with a distinctive aromatic odor and sweet taste, 2.50-2.80% of water content, 5-6 second in flow time showing good flow properties, 32.21-33.42 º in angle of repose showing powder easy to flow, and compressibility index of 10% -18%. The particle size distribution of dry chayote powder was fine powder with particle size around 0.5-0.7 mm. Statistical analysis results showed there were no significant effect of the drying temperature variations on the physical properties of dry chayote powder. The conclusion of this study is drying temperature variations (100 ºC, 80 ºC, dan 60 ºC) does not affect the physical properties of dry chayote powder.